Minyak Daun Cengkeh Sebagai Bioaditif Bahan Bakar Solar Perahu Nelayan Untuk Menurunkan Konsumsi Bahan Bakar - Bulan Purnama; Alifia Pratiwi Herman; Muhammad Rif’at; Muhammad Rahmat Ramadhana; Farrel Risai; Hutabri Setiyoputra Suharto (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2021)
One of the efforts made to reduce exhaust emissions or pollution produced by petroleum-fueled engines is to make the combustion reaction take place perfectly on fishing boats by enriching the oxygen source in the fuel, namely by adding additives with compounds that are rich in oxygen and can be dissolved in the fuel. burn it. One alternative additive that is good and environmentally friendly and has been developed is to use essential oils. The purpose of this study focused on the potential of clove leaf essential oils, namely eugenol, caryophyllene, rhodinol and citronellal as bio-additives in diesel fuel to reduce emissions resulting from the combustion process in fishing boat engines. The bio additive materials used in this study were clove leaf oil and eugenol and caryophyllene compounds contained in clove leaf oil. The emission test results from the addition of clove leaf oil bio-additives reduced CO levels by 30%, NO 36%, SO 12% and total particulates 30%, Eugenol reduced levels of CO 37%, NO 38%, SO 32%, and total particulates 40%, Caryophyllene reduced levels of CO 24%, NO 19%, SO 33% and total particulates 16%. So from the addition of essential oil from clove leaves is an effective solution in saving fuel and reducing emissions.